Psychosocial factors associated with smoking behavior among secondary school adolescents in Ibadan metropolis . (2005)
"The use of tobacco among adolescents has been recognized as prominent problem behaviour in recent years. This study investigated the psychosocial factors associated with smoking behaviour among secondary school adolescent smokers (N=200) in Ibadan metropolis. One hundred and forty six (73%) were males while fifty four (27%) were females. The study is a cross-sectional survey which adopted the expost facto research design. Each participant was administered a questionnaire consisting of the demographics, self esteem, locus of control, index of family relations and smoking behaviour scale. Only student smokers available at the high risk areas were selected to participate in the study. Result indicated that of al/ the psychosocial factors, only self esteem and family relations had individual significant contribution to smoking• behaviour of the adolescents (B= -.60, P<.05; B= -.43, P<.05 respectively) while other factors (locus of control, parental education, parental occupation, religious affiliation, and sex) did not. However, all the psychosocial variables jointly significantly predicted adolescent smoking behaviour contribution 36% of the variance (R2 =0.36, p<.05). The regression analysis also showed that locus of control and self-esteem alone jointly significantly contributed 32% (R2 = 0.32, p<.05) while Parental occupation and education, family relationship as well as sex jointly contributed 0.8% (R2 = 0.08, p<.05) to the explanation of the variance observed in smoking behaviour among adolescents. Further analysis showed that adolescent with low self esteem' engaged more in smoking than those with high self esteem (t (198)=7.9; p<.0001). Findings suggested that psychological factors other than social factors are more serious predictors and maintenance factor of smoking behavior among adolescents. It is thus recommended that personnel working on smoking behaviour control and management should seriously consider psychological factors such as self esteem and locus of control, as well as some social factors such as family relationship while packaging their interventions "